Risperidone-Induced Acute Laryngeal Dystonia: A Case Report - Alkharboush, Ghassan A. (Am J Case Rep, 2020)
Patient: Female, 28-year-old Final Diagnosis: Acute laryngeal dystonia Symptoms: Shortness of breath Medication:— Clinical Procedure: Benzotropine administration Specialty: General and Internal Medicine • Psychiatry OBJECTIVE: Unusual clinical course BACKGROUND: Antipsychotic medications are associated with multiple adverse effects, including metabolic syndrome, prolonged QT interval, and extrapyramidal symptoms. Acute laryngeal dystonia (ALD) is a rare and lethal form of extrapyramidal reaction. CASE REPORT: A 27-year-old woman with schizophrenia on risperidone presented to our Emergency Department with a sensation of choking and respiratory distress, mimicking a panic attack. She developed a generalized dystonic reaction in the hospital, leading to diagnosis risperidone-associated ALD as a cause of her initial problems. She was discharged with an emphasis on being compliant with anticholinergic medication. However, her persistent respiratory symptoms prompted us to revisit the management plan. Her risperidone dose was tapered down to discontinue and an alternate drug was chosen. CONCLUSIONS: ALD must be considered as a differential diagnosis when patients on antipsychotic medications present with respiratory distress. Our case highlights the association of ALD with an atypical antipsychotic agent, risperidone. Prompt recognition of this entity is necessary to prevent complications and guide definitive management.